TRIK DAN TIPS BERHASIL DALAM MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V DAN VI MIS SINGKARAK KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - Elan Halid; Mega Putri; Zona Rida Rahayu (ASOSIASI IDEBAHASA KEPRI, 2021)
Indonesian also functions as the language of instruction in educational institutions, from the lowest educational institutions (kindergartens) to the highest educational institutions (tertiary institutions) throughout Indonesia, except for areas that still use regional languages ??as their mother tongue. In the world of Indonesian education, especially in the curriculum regardless of year, there must be Indonesian language learning subjects. Various problems solve partner problems, namely students who have difficulty understanding Indonesian language lessons because some students think that Indonesian subjects are very difficult subjects and students have not seen good tips and tricks for mastering Indonesian subjects, especially in facing national exams. (UN). The implementation of service activities is carried out by providing outreach to students in grades V and VI of the Singkarak Private Madrasah Ibtidaiyah with the method of lecturing, question and answer, and practice answering exam questions in Indonesian subjects. In general, participants can receive the material that has been presented by the resource person as an alternative solution to increase students' knowledge of tricks and tips that work in Indonesian subjects and can answer practice questions. Performance indicators of socialization activities, question and answer, and practice in answering exam questions can be seen from the level of student knowledge that is getting better. With the presentation of material from several resource persons, students are able to understand and see how to quickly answer Indonesian language exam questions because in essence there are 4 strategies for mastering the Indonesian National Examination (UN), namely looking for keywords, see the answer options first, Memorize characteristics, and do the fairly difficult problems first.